The Effectiveness of Utilization WhatsApp Application As Media Discussion (Study of â€œKelas Prestasiâ€ Community in the Scope of University of Bengkulu) - Usman, Ujang; Arwani, Marwan; Samosir, Fransiska Timoria (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2020)
Background of the study: The student in â€œKelas Prestasiâ€ Community in University Bengkulu uses the WhatsApp in daily communication in discussion.Purpose: The research about